If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3x + -5) + -4(x + -2) = 5(x + -1) + -1 Reorder the terms: 2(-5 + 3x) + -4(x + -2) = 5(x + -1) + -1 (-5 * 2 + 3x * 2) + -4(x + -2) = 5(x + -1) + -1 (-10 + 6x) + -4(x + -2) = 5(x + -1) + -1 Reorder the terms: -10 + 6x + -4(-2 + x) = 5(x + -1) + -1 -10 + 6x + (-2 * -4 + x * -4) = 5(x + -1) + -1 -10 + 6x + (8 + -4x) = 5(x + -1) + -1 Reorder the terms: -10 + 8 + 6x + -4x = 5(x + -1) + -1 Combine like terms: -10 + 8 = -2 -2 + 6x + -4x = 5(x + -1) + -1 Combine like terms: 6x + -4x = 2x -2 + 2x = 5(x + -1) + -1 Reorder the terms: -2 + 2x = 5(-1 + x) + -1 -2 + 2x = (-1 * 5 + x * 5) + -1 -2 + 2x = (-5 + 5x) + -1 Reorder the terms: -2 + 2x = -5 + -1 + 5x Combine like terms: -5 + -1 = -6 -2 + 2x = -6 + 5x Solving -2 + 2x = -6 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -2 + 2x + -5x = -6 + 5x + -5x Combine like terms: 2x + -5x = -3x -2 + -3x = -6 + 5x + -5x Combine like terms: 5x + -5x = 0 -2 + -3x = -6 + 0 -2 + -3x = -6 Add '2' to each side of the equation. -2 + 2 + -3x = -6 + 2 Combine like terms: -2 + 2 = 0 0 + -3x = -6 + 2 -3x = -6 + 2 Combine like terms: -6 + 2 = -4 -3x = -4 Divide each side by '-3'. x = 1.333333333 Simplifying x = 1.333333333
| X^2-(2b-1)x+(b^2-b-2a)=0 | | x-0.20x=96 | | 5x-87+11x=121 | | 6z-61=4z-33 | | -3(2j-6)+10=-6j-12(2j-3) | | -2(2s-6)-12=-2(8s+0)-2 | | -3(t-3)+5t=8t-3 | | -5x-2(x+24)=-90 | | 5000=-16t^2+880t+40 | | x+24+x+32=180 | | 4y+90=180 | | 3(1+11n)=-3(-8n-12)+9n | | 5x^2-60x+40=0 | | 3x-5(x-2)=-4+2x-18 | | 13x+6=12x+14 | | x+24+x+3=180 | | -249-24x=159 | | 4.9=6.4-0.5x | | -180+8x=-160+6x | | 30=-16t^2+80t+5 | | 7t-90=2t-15 | | (5x+7)(2x+1)=85 | | -76-4x-x=59 | | -80=7x+2(-2x-31) | | 2x+24=576 | | 5y^2+5y-9=0 | | 9y-65=y+39 | | 8x-10=-4+2x-18 | | -2(12m-6)-6m=10(3-3m) | | 4(4x-5)-1=16x-21 | | -11=a-5/5 | | 11-n/5=19 |